2020
DOI: 10.1007/s11926-020-0886-x
|View full text |Cite
|
Sign up to set email alerts
|

Complexities in Genetics of Psoriatic Arthritis

Abstract: Purpose of the Review To provide a general overview and current challenges regarding the genetics of psoriatic disease. With the use of integrative medicine, multiple candidate loci identified to date in psoriatic disease will be annotated, summarized, and visualized. Recent studies reporting differences in genetic architecture between psoriatic arthritis and cutaneous-only psoriasis will be highlighted. Recent Findings Focusing on functional pathways that connect previously identified genetic variants can inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…It has been postulated that the initiation of PsA occurs after triggering by environmental factors in gut, entheses, or skin in patients who are genetically more susceptible to development of this disease (37). The genetics of PsA have been reviewed in detail (38)(39)(40)(41). In short, both HLA and non-HLA coding genes are associated with PsA.…”
Section: Initiation Of Psoriatic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that the initiation of PsA occurs after triggering by environmental factors in gut, entheses, or skin in patients who are genetically more susceptible to development of this disease (37). The genetics of PsA have been reviewed in detail (38)(39)(40)(41). In short, both HLA and non-HLA coding genes are associated with PsA.…”
Section: Initiation Of Psoriatic Arthritismentioning
confidence: 99%
“…HLA coding genes linked to PsA have supported the role for peptide binding and T cell activation in PsA pathogenesis (40). In the non-HLA coding groups genes are related to innate immunity, cytokines (TNF, IFN, and IL-23/17) and antigen processing and presentation (38). However, genes that are specifically associated with development of PsA in PsO patients remain scarce (39).…”
Section: Initiation Of Psoriatic Arthritismentioning
confidence: 99%
“…The rapid emergence of affordable high-throughput technology will likely lead to the discovery of genetic factors that may lead to a more in-depth comprehension of mechanisms underlying the different phenotypical patterns of PsA and more precise profiling of axPsA patients. Such findings may hopefully support clinicians in choosing for each patient the treatment with higher likelihood efficacy (Rahmati et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, although significant epidemiological clinical and prognostic differences between axPsA and ankylosing spondylitis (AS) have been highlighted in several studies (Jadon et al, 2017 ; Feld et al, 2018 ), it is still a matter of debate whether axPsA and AS are different phenotypes on the spectrum of the same disease, or they are different diseases with overlapping features (Feld et al, 2018 ). Genetic studies were called into question to understand the basis of such differences and overlapping aspects (Rahmati et al, 2020 ). In particular, the prevalence of HLA-B27, the key genetic marker of AS, was demonstrated to be lower in patients with PsA (20 vs. 95%), although among PsA patients, those with axPsA were significantly more frequently HLA-B27-positive compared with those without axial involvement ( P < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis severity, psoriatic nail disease, infection, trauma, stress, and obesity are considered risk factors for the development of PsA; however, it remains unclear whether nail involvement is a predictor of PsA or an early manifestation of PsA [31]. Genetic studies have found PsA to have a strong genetic component [32][33][34] and have linked several human leukocyte antigen (HLA) genotypes to PsA (e.g., HLA-B*27) [35].…”
Section: Pathophysiology Of Psamentioning
confidence: 99%